SISTEM SAPAAN BAHASA SUNDA - , Cucu Suminar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research of Sundanese address system is aimed at describing the form, classifying term of address based on its meaning, explaining factors that influence the use of various types of address, explaining the function of address, and describing the rule of the use of address. The method used in this research is listening method and noting technique. In analyzing data, intralingual and extralingual corresponding are used. Based on its form Sundanese address can be classified based on its morphological feature and syntactic feature. Referring to its meaning or its semantic feature, Sundanese address includes address related to proper name, personal pronoun, kinship, occupation or profession, religion, friendship, rapport, and honor. There are several factors influencing the choice of address form in Sundanese, namely situation, intimacy or rapport, age, sex, marital status, and ethnical orientation. Viewed from its function, Sundanese address can be classified into marking social relation, showing affection, showing anger, asking attention, educated, and honor. The rule of address use covers alternation rule and coocurence rule. The alternation rule relates to a number of alternatives such as situation which includes the age of child speech partner, teenage speech act, or adult, sex, married or single, title, and social status of speech partner. The coocurence rule explains the use of one form of address that can be followed by other address form.